A review of cervical cancer in HUSM for 15 years period, from 1996 to 2010 - Narawi, Mohamad Maulizal Nawi @ (2014)
This study was designed to review the cervical cancer cases that presented to HUSM between 1996 to 2010. In specific, it involved determination of characteristic of cervical cancer cases in HUSM during this period. This study also compared the epidemiology trend of cervical cancer in HUSM in the second and third 5 years period of the study. Apart from that, it also determined and compared the associated factors between early versus advanced cervical cancer in relation to morbidity and mortality in HUSM during the period This retrospective study was conducted in HUSM for a period between 1996 to 2010. It covered all the 221 recorded case of cervical cancer that been admitted and primarily treated in HUSM . All their medical records were review and related information were entered in a standard data collection form. There were 221 cervical cancers cases involved in this study. The vast majority were Malay ethnic. Base on Malaysian and Kelantan population study, it can be concluded that Chinese ethnic group had slightly higher risk to developed cervical cancer. 72% of patients were from Kelantan and 25% from Terengganu. Most came from the capital city of Kelantan and Terengganu due to its high population. The mean age of the patients diagnosed to have cervical cancer in this study was 54 years old. The majority of the patients were in the 50th decade of their life (age 50-59 years old). Generally patients that presented in this study were healthy patients with no comorbid (84%). All of the patients were married. Vast majority (95.5%) were multiparity with average parity of 5. More than half patients were postmenopausal (55.7%). There were very high correlation between not doing any pap smear to cervical cancer as 90% of patient never did any pap smear before. However poor corelation between smoking (5%) and family history of malignancy(2.7%) to cervical cancer in this study. Obtaining sexual history were not an easy task in this population. It was considered as humilation and for some as dysrespect. Thus it was very highly likely that the number of patients or partners with multiple sexual partners will be far less then it really were. Meanwhile, mean age of sexual exposure was 20 years old. Most patients were referred to HUSM by terteiry centre for further treatment 54%. Most patients either presented with PMB (38.9%) or PCB (38.5%). Majority of patients presented during stage 2B (31.2%) and 3B (25.3%). As per other underdeveloped country, 67.4% of cases were in their late stage. Only 32.6% came when the diseases still early. 78% were SCC, 15.4% were adenocarcinoma. Base on limited CT scan report 84.6% were locally advance disease. Correspond to stage at presentation 61.5% were treated with Rtx/ CCRT. Only 60 patients undergo surgical intervention with 80% without any complication. Of that, 77% had no dyscrepancy between clinical and surgical staging. 120 patients were disease free. The average were 36 months. However up to 65% defaulted their follow up and never turn up thereafter. Most patients that had recurrent presented in >12 to 36month periods, so did the death. However 49 patients having progressive disease. Up to 13% of patient that died due to non cervical cancer causes The comparison between year 2001-2005 and 2006-2010 shows few promising data. There were slight increased patients from terengganu (20 vs 28%) and coincidental reduce in chinese patient from 13 to 6.6%. The risk factor were comparable to general population of the study. In term of stages, the prominant changes were double the case of 1b2 disease ( from 6 to 12%). This were likely influenced the increased surgery and adjuvant Rtx/CCRT in 2006-2010 periods. Early recurrent (within 6-12 months periods) were almost triple (from 4.6 to 13.9% ). The exact cause were unknown. The death were also different,where by in the earlier year had only 53% death within 36 months,while in later years the percentage of death at the same periods were 72%. Regarding the factor between early and late disease. It was noted that patients with early stage were majority in 40th decades, whereby the late stage group were majority in 50th decades. Patients from Terengganu had 3 times likely late stage compare those from Kelantan. So did patients that referred by terteiry centre (with Odd 2.5) Postmenopausal were more associates with late disease with odd more than 2.5 times. The late stage groups had higher defaulter percentage in the first year of diagnosis (41% compare to 22% in early stage). There were significantly more death at late stage arm. The majority death in late stage were within 6 months (46%), while in early stage were in >12 to 36months periods (29.6%).